Excitation temperatures in plasma of underwater disharges between iron granules - Murmantsev, A.; Veklich, A.; Boretskij, V. (Вопросы атомной науки и техники, 2020)
This paper deals with development of optical emission spectroscopy techniques for diagnostic of underwater discharge plasma between iron granules. The difficulties in selection of iron spectral lines, as well as the approximation of their profiles for determination of excitation temperature are discussed. A method of spectral lines resolving with close wavelengths is considered. Simulation of a narrow rangeof the plasma emission spectrum is carried out to estimate the excitation temperatures in underwater discharge plasma. Представлена стаття присвячена розробці методів оптичної емісійної спектроскопії для діагностики плазми підводного розряду між гранулами заліза. Обговорено труднощі селекції спектральних ліній заліза, а також апроксимації їх профілів для визначення температури заселення. Розглянуто метод розділення спектральних ліній з близькими довжинами хвиль. Для оцінки температур заселення в плазмі підводного розряду виконано моделювання вузької ділянки спектру випромінювання плазми при різних температурах. Представленная статья посвящена разработке методов оптической эмиссионной спектроскопии для диагностики плазмы подводного разряда между гранулами железа. Обсуждены трудности селекции спектральных линий железа, а также аппроксимации их профилей для определения температуры заселения. Рассмотрен метод разрешения спектральных линий с близкими длинами волн. Для оценки температур заселения в плазме подводного разряда выполнено моделирование узкого участка спектра излучения плазмы при различных температурах.